Safety and feasibility of robotic major hepatectomy for novice surgeons in robotic liver surgery: A prospective multicenter pilot study. (December 2020) - Choi, Sung Hoon; Han, Dai Hoon; lee, Jin Ho; Choi, YoungRok; Lee, Jae Hoon; Choi, Gi Hong
Abstract: Background: Robotic liver resection has not yet been widely implemented. We aimed to evaluate the feasibility and safety of robotic major liver resection by performing a prospective multicenter study. Methods: From July 2017 to December 2018, five surgeons from five tertiary hospitals who were novices in robotic liver resection but experienced in open and laparoscopic liver resection performed 46 cases of robotic major anatomical liver resections. Perioperative clinical data and surgical data, including detailed procedure times were prospectively collected. All operations were performed according to a protocol for unify surgical techniques and instruments. Results: Twenty-two cases of left hemihepatectomy, one case of extended left hemihepatectomy, 14 cases of right hemihepatectomy, two cases of right anterior sectionectomy, six cases of right posterior sectionectomy, and one case of central bisectionectomy were performed. The most common indications were hepatocellular carcinoma (21 cases) followed by intrahepatic duct stones (10 cases), intrahepatic cholangiocellular carcinoma (7 cases), liver metastases (3 cases), intraductal papillary neoplasms (2 cases), sarcoma (1 case), mucinous cystic neoplasm (1 case), and hemangioma (1 case). Surgical resection margins for all tumor cases were negative. The mean operation time was 378.58 ± 124.31 (190–696) minutes and the estimated intraoperative blood loss was 276.67 ± 397.41 mL (range, 10–2600 mL). Overall complications developed in 16 cases (34.8%). There were three cases of severe surgical complications (Clavien-Dindo classification of III or more). Only one of 46 cases was converted to conventional open left hemihepatectomy because of bleeding. The mean hospital stay was 7.3 ± 2.5 (4–18) days. Conclusions: The results of this study indicate that robotic anatomic major liver resection can be safely performed by robotic beginners who are advanced open and laparoscopic liver surgeons. Highlights: The first prospective multicenter study to evaluate the feasibility and safety of robotic liver resection. Increased dexterity of robotic instruments is one of the greatest advantages for delicate tasks. Parenchymal transection of robotic liver surgery is feasible using a well-established protocol. Even a beginner of robotic surgery with sufficient liver surgery experience can safely perform robotic major liver resection.